Perceived Value and Purchase Intention Among Young Adults Perfume Consumers: A Mixed-Method Exploration - Rembulan, Cicilia Larasati; Sanjaya, Ersa Lanang (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: The cosmetics industry including perfume was one of the industries that contributed to the economy in Indonesia (3.83% in the first quarter of 2023). This made the perfume industry a worthy field to discuss. Purpose: The objective of this study is to see the influence of dimensions of perceived value on the intention to purchase perfume X in young adults. Design/methodology/approach:  The research design used was a mixed method. The online survey was conducted with 217 early adulthood (18-25 years). Quantitative data analysis used PLS SEM. Qualitative data was obtained by interviewing 24 respondentsFinding/Result: In study 1, it was found that social and emotional perceived value have an influence on the intention to buy product X. Based on study 2, it was found that the emergence of certain memories or nostalgia and the influence of friends and praise from people closest to them were important. Conclusion: In the context of teenagers and non-luxury perfumes, emotional and social perceived value are important because they will be related to purchase intentions. Originality/value (State of the art):  In this study, it was found that social and emotional perceived value are important things related to purchase intention, while quality and price have no influence. Keywords: perceived value, intention to purchase, perfume industry, early adulthood, mixed method